Analisis Pengaruh Daya Tarik Iklan dan Kelompok Acuan terhadap Perpindahan Merek pada Laptop Toshiba dengan Citra Merek Sebagai Variabel Intervening (Studi Kasus pada eks-Konsumen Toshiba di Kota Semarang) - Hanif, Muhammad Haidar; Soesanto, Harry (Diponegoro Journal of Management, 2017)
Tight Industrial Competition makes Toshiba brand laptops has declined percentage in Top Brand Index for three consecutive years although its position is currently still ranked second, but at the same time other brands have increased their Top Brand Index. This study aims to analyze the influence of advertise appeals variable and the reference group into brand switching on Toshiba laptops with brand image as intervening variable. The technique used in sampling on this study is non probability sampling with 130 respondents who have the criteria ever used Toshiba brand laptop and switch into other brands. The analysis method used is maximum likelihood test with AMOS program 22.0 version.The results showed that the advertisement appeals and reference groups have a positive effect on brand switching either directly or through brand image variables. Where the variable of advertisment appeal has the greatest influence on brand switching, followed by brand image and the last is the reference group.